2010
DOI: 10.1021/bi101665s
|View full text |Cite
|
Sign up to set email alerts
|

Tripping the Light Fantastic: Blue-Light Photoreceptors as Examples of Environmentally Modulated Protein−Protein Interactions

Abstract: Blue light photoreceptors play a pivotal role in detecting the quality and quantity of light in the environment, controlling a wide range of biological responses. Several families of blue-light photoreceptors have been characterized in detail using biophysics and biochemistry, beginning with photon absorption, through intervening signal transduction, to regulation of biological activities. Here we review the Light Oxygen Voltage (LOV), Cryptochrome (CRY) and sensors of Blue Light Using FAD (BLUF) families, thr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

4
218
0
3

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 145 publications
(228 citation statements)
references
References 161 publications
4
218
0
3
Order By: Relevance
“…This result implies that the compressibility changes during the reaction. From the pressure dependence of the amplitude, the compressibility change of two short-lived intermediate (I 1 and I 2 ) states were determined to be +(5.6 ± 0.6) × 10 −2 cm 3 ·mol −1 ·MPa −1 for I 1 and +(6.6 ± 0.7)×10 −2 cm 3 ·mol −1 ·MPa −1 for I 2 . This result showed that the structural fluctuation of intermediates was enhanced during the reaction.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…This result implies that the compressibility changes during the reaction. From the pressure dependence of the amplitude, the compressibility change of two short-lived intermediate (I 1 and I 2 ) states were determined to be +(5.6 ± 0.6) × 10 −2 cm 3 ·mol −1 ·MPa −1 for I 1 and +(6.6 ± 0.7)×10 −2 cm 3 ·mol −1 ·MPa −1 for I 2 . This result showed that the structural fluctuation of intermediates was enhanced during the reaction.…”
mentioning
confidence: 99%
“…Photosensor proteins are an important example. They have light-sensing domains and function by using the light-driven changes in domain-domain interactions (1). The sensor of blue light using FAD (BLUF) domain is a light-sensing module found widely among the bacterial kingdom (2).…”
mentioning
confidence: 99%
“…Photolyase activation involves two cofactors, the catalytic FAD in a two-electron reduced FADH-state and an antennae cofactor that can vary in identity (i.e., MTHF, HDF, flavins). Activation of photolyases is achieved by absorption of UV-A light by the antennae cofactor, which induces electron transfer from FADHto the DNA lesion (3,8). Importantly, a second electron transfer pathway exists in photolyases and is composed of a series of three Trp residues (Trp triad) forming a pathway from the catalytic FAD to the protein surface (Fig.…”
Section: Cry Photochemistrymentioning
confidence: 99%
“…These debates center on sequence conservation within the CRY/ photolyase family (CPF). Despite high sequence similarities, CPF members demonstrate functions ranging from DNA repair enzymes (photolyases) to blue light-regulated growth, development, and circadian rhythms in diverse organisms (CRYs) (3). In all cases, CPF function hinges upon a bound flavin adenine dinucleotide (FAD) cofactor that undergoes interconversion between several redox states (Fig.…”
mentioning
confidence: 99%
See 1 more Smart Citation